2013
DOI: 10.1021/np400638r
|View full text |Cite
|
Sign up to set email alerts
|

Diterpenoids and Sesquiterpenoids from the Roots of Illicium majus

Abstract: Five new diterpenoids (1-5), five new sesquiterpenoids (6-10), and three known compounds (11-13) were isolated from the roots of Illicium majus. Their structures were elucidated by extensive spectroscopic analysis. The absolute configuration of 1 was assigned by X-ray crystallography, whereas those of the 1,2-diol moieties in 3 and 4 were determined using Snatzke's method. The abietane acids 1, 2, 11, 12, and 13 displayed antiviral activity against the Coxsackie B3 virus, with IC50 values of 3.3-51.7 μM/mL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 32 publications
1
15
0
Order By: Relevance
“…Similarly, studies carried out with essential oils from SA also showed interesting results with respect to its antiviral effects. Studies Wang et al, 2013) carried out with the anise oil along with two other essential oils (dwarf-pine oil and chamomile oil) against different types of thymidine-kinase such as thymidine-kinase-positive (aciclovir-sensitive) and thymidine-kinasenegative (aciclovir-resistant) herpes simplex virus Type 1 (HSV-1) showed that all these essential oils have antiviral activity against the aciclovirsensitive HSV strain KOS and aciclovir-resistant clinical HSV isolates as well as aciclovir-resistant strain Angelotti, through interrupting the adsorption of herpes viruses. This is different from the mode of action of aciclovir, which is effective after attachment inside the infected cells.…”
Section: Antiviral Effects Of Active Constituents From Samentioning
confidence: 99%
“…Similarly, studies carried out with essential oils from SA also showed interesting results with respect to its antiviral effects. Studies Wang et al, 2013) carried out with the anise oil along with two other essential oils (dwarf-pine oil and chamomile oil) against different types of thymidine-kinase such as thymidine-kinase-positive (aciclovir-sensitive) and thymidine-kinasenegative (aciclovir-resistant) herpes simplex virus Type 1 (HSV-1) showed that all these essential oils have antiviral activity against the aciclovirsensitive HSV strain KOS and aciclovir-resistant clinical HSV isolates as well as aciclovir-resistant strain Angelotti, through interrupting the adsorption of herpes viruses. This is different from the mode of action of aciclovir, which is effective after attachment inside the infected cells.…”
Section: Antiviral Effects Of Active Constituents From Samentioning
confidence: 99%
“…angustanoic acid F) 21 and majusanic acids ( e.g. majusanic acids B, D, E and F) 22 have shown to possess antiviral activity against Coxsackie B viruses.…”
Section: Resultsmentioning
confidence: 99%
“…Even though all parts of the tree have been classified as toxic by botanists, the roots, leaves and bark of I. majus are used in folk medicine to promote blood circulation, relive pain, dispel wind, and treat rheumatic arthritis [1,2] . To date, various seco‐prezizaane‐type sesquiterpenes, diterpenes, prenylated C 6 –C 3 compounds, and lignans have been isolated from the different parts of this plant, [3,4] and among them, only three glycosides have currently been reported from this plant [1–6] . In our continuing work to discover new bioactive constituents from the Illicium genus, we carefully investigated the high‐polarity components (BuOH fraction) of the ethanol extract of I. majus , expecting to separate more natural active products.…”
Section: Introductionmentioning
confidence: 99%